Public Service Innovation Through the Implementation of the E-Boarding Pass System on Long Distance Trains at PT. Indonesian Railways (Persero) - Muhammad Ardi Yudhanto; Asep Nurjaman (Jurnal Public Policy, 2022)
This article aims to find out how to innovate the implementation of the e-boarding pass system at PT. Kereta Api Indonesia (Persero) whether delivered well to train users or not, until they switch from conventional ticket printing to ticket printing system via e-boarding pass with smartphone. The problem is focused on the e-boarding pass system which the author considers very innovative in utilizing technology that is growing every year, especially services must think how they optimize their services, one of which is by utilizing technology in changing the old system that is considered irrelevant to use and there are always problems in it by overhauling certain aspects such as purchasing and printing tickets manually through tellers are being changed to online based system ranging from purchasing or printing tickets. To approach the problem of the author using a theoretical reference from Cresswell by using a type of qualitative research that is a literature study that uses books and other literature as the main object, because the author uses literature research then the data obtained through books and literature that supports research. This paper concludes that policy innovations in the implementation of the e-boarding pass system whether it goes as expected.